The Implementation of Mind Mapping-Assisted Problem-Based Learning Model in Geography Lessons to Enhance Critical Thinking Skills of SMA: Penelitian - Elsia Fitri Hasanah; I Gede Astra Wesnawa; Ida Bagus Made Astawa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The low level of critical thinking skills among students in geography lessons in class XI.F at SMA Negeri 3 Singaraja is a problem that needs to be solved. In this regard, a classroom action research (CAR) study was conducted to analyze the application of the Mind Mapping-assisted PBL model in geography lessons and to improve critical thinking skills through the Mind Mapping-assisted Problem-Based Learning model. This study used Kemmis & McTaggart's Classroom Action Research (CAR) design, which was carried out in two cycles with 42 students in class XI F of SMA Negeri 3 Singaraja as the research subjects. Data were collected through observation and tests, then analyzed using descriptive quantitative methods.. The results showed that the application of the Mind Mapping-assisted Problem-Based Learning model went well. Students' critical thinking skills increased by 22.20%. Thus, the Mind Mapping-assisted Problem-Based Learning model is efficacious in improving students' critical thinking skills in geography at SMA Negeri 3 Singaraja.